Influenza Vaccine - Nomsiri, Banchong (Journal of Health Science of Thailand, 2018)
Influenza is a disease that commonly occurs in Thai population but usually does not cause serious health conditions among Asians. Recent emerging of avian influenza disease in human in several Asian countries including Thailand threatened the public with impending disaster. Avian influenza patients were severely ill and had high mortality rate. Although belonging to the same family, avian influenza virus strain is close to but quite distinct from currently circulating seasonal influenza viruses. The use of influenza vaccine in health workers is a preventive measure. This article summarizes and updates knowledge on influenza vaccine for health personal and the public.